2018
DOI: 10.1172/jci94158
|View full text |Cite
|
Sign up to set email alerts
|

A TLR/AKT/FoxO3 immune tolerance–like pathway disrupts the repair capacity of oligodendrocyte progenitors

Abstract: ers by interactions of FoxO3 with the chromatin-remodeling factor Brg1 and the TF Olig2, which are involved in control of OPC differentiation (14-16). Hence, central myelination failure is regulated by a noncanonical TLR4/AKT/FoxO3 signaling pathway utilized by bHAf to induce a tolerance-like state that selectively constrains OPC maturation and myelination. ResultsNeonatal hypoxic-ischemic WMI promotes MDa HA depolymerization. To investigate the status of MDa HA in chronic neonatal WMI, we employed our preterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 54 publications
2
41
0
Order By: Relevance
“…We previously reported that the activities of PH20, Hyal2, and Hyal5 blocked OPC maturation when expressed by OPCs in vitro, with PH20 having the greatest inhibitory activity. We also found that digestion products of HA in a specific size range blocked remyelination in vitro and in vivo (Preston et al, ; Srivastava et al, ). Hyal5 has not been detected in OPCs or in the CNS (Preston et al, ) while PH20 RNA has been reported to only be transiently expressed by OPCs or other cells, especially following CNS insults (Hagen et al, ; Preston et al, ; Sherman & Back, ; Sloane et al, ; Xing et al, ).…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…We previously reported that the activities of PH20, Hyal2, and Hyal5 blocked OPC maturation when expressed by OPCs in vitro, with PH20 having the greatest inhibitory activity. We also found that digestion products of HA in a specific size range blocked remyelination in vitro and in vivo (Preston et al, ; Srivastava et al, ). Hyal5 has not been detected in OPCs or in the CNS (Preston et al, ) while PH20 RNA has been reported to only be transiently expressed by OPCs or other cells, especially following CNS insults (Hagen et al, ; Preston et al, ; Sherman & Back, ; Sloane et al, ; Xing et al, ).…”
Section: Introductionmentioning
confidence: 68%
“…Vcpal (e.g., Sloane et al, 2010;Preston et al, 2013, pp. 266-80;Srivastava et al, 2018). We found that the effects of S3 were reversed if cultures were treated with 25 U of recombinant PH20 (Figure 4d,f)…”
Section: Selective Inhibition Of Hyaluronidase Activity Promotes Opmentioning
confidence: 79%
See 3 more Smart Citations